Kuat Tekan Dan Porositas Beton Campuran Crumb Rubber Dan Abu Sekam Untuk Material Perkerasan Kaku Di Tanah Gambut - Mia Qoryati; Monita Olivia; Gunawan Wibisono (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
This study aims to study the compressive strength and porosity of PCC concrete and PCC-CR-RHA concrete. PCC concrete as a control and PCC-CR-RHA concrete that contains 5% of crumb rubber and 10% of rice husk ash. These concretes exposed to peat water with flexural strength according to Bina Marga 2018 standard regarding rigid pavement of 4.5 MPa and 35 MPa compressive strength. The tests were carried out after speciments were cured on peat water for 0, 7, and 28 days. The test results showed that the compressive strength of PCC concrete was 32.065 MPa, higher than the compressive strength of PCC-CR-RHA at 28 days. While the porosity of PCC concrete was 7.204%, lower than the porosity of PCC-CR-RHA at 28 days. The test results of PCC concrete compressive strength at the age of 28 days for peat water curing increased by 10.01% as well as PCC-CR-RHA concrete, which increased by 6.79%. PCC concrete porosity values at the age of 28 days for peat water curing decreased by 36.90% as well as PCC-CR-RHA concrete, which decreased by 43.15%. Based on the results of tests conducted, both types of concrete have good compressive strength and porosity when exposed to peat water.Keywords: Compressive strength, porosity, crumb rubber, rice husk ash, rigid pavement, peat soil.